Pengaruh Leverage, Pertumbuhan Penjualan dan Ukuran Perusahaan terhadap Kinerja Keuangan: Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Putri Nurul Arifin; Rachmat Arif (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This study aims to analyze leverage as proxied by the debt to equity ratio, sales growth and firm size to financial performance as proxied by return on asset. This research was conducted on companies in the Consumer Non-Cyclicals Sector Food and Beverage Sub Sector, which were listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling method in this research used a purposive sampling method with a sample of 30 non-cyclical consumer sectors, food and beverage sub-sectors that met the sample criteria. This study used multiple linear regression analysis techniques and used SPSS statistical test tool version 22.0. The results of this study show that the variable leverage and firm size have a negative and significant effect on return on assets, while sales growth does not affect return on assets.